Bilingualism in language education in secondary schools of the Republic of Tuva - Arefiev, Alexander L.; Bakhtikireeva, Uldanai M.; Sinyachkin, Vladimir P. (The New Research of Tuva, 2021)
The article examines the contemporary situation in bilingual language education within the school system of the Republic of Tuva, comparing it with the same processes throughout Russia. In the Post-Soviet period, all regions saw the rise of an ambiguous state within language education due to specific demography and language policy. The history of changes in language education in Tuva is inseparable from the opposing moves in Russia’s national and linguistic policy. Alongside with the decisive and positive transformations in Tuvan culture, some losses were also inevitable, such as that of sociocultural and linguistic vitality of Tuvan language within the educational system. Seen in the context of the developments of all minority languages both in Russia and around the world, this process is most likely historically determined. Unlike other ‘ethnic republics’ of Russia, Tuva has long remained mostly monolingual. Nevertheless, over 80 years of the history of Tuva within Russia means that at least two generations of Tuvans have grown up in the new sociocultural environment. Numerous changes in linguistic situation alongside with the absence of continuity in the policy of Tuvan bilingualism (largely due to similar lack of continuity in the language policy of Russia) gave rise to a complex phenomenon of collective bilingualism. Within the system of education in Tuva, the tendency is towards a redistribution of spheres of usage of Russian and Tuvan languages. Just as any other language in Russia, the latter obviously does not stand the competition against the former, especially given that since 2018 it has practically stopped functioning as a language of education. Moreover, the early introduction of Russian in bilingual pre-school education also narrows down the sphere of use of Tuvan as a language in the subordinate position. This disbalance in the bilingual situation can potentially lead to disruptions in the intergenerational transfer of Tuvan culture.